2008
DOI: 10.1063/1.2979702
|View full text |Cite
|
Sign up to set email alerts
|

Ti-based nonalloyed Ohmic contacts for Al0.15Ga0.85N∕GaN high electron mobility transistors using regrown n+-GaN by plasma assisted molecular beam epitaxy

Abstract: Development of high-performance fully depleted silicon-on-insulator based extended-gate field-effect transistor using the parasitic bipolar junction transistor effect Appl. Phys. Lett. 101, 133703 (2012) Abnormal interface state generation under positive bias stress in TiN/HfO2 p-channel metal-oxide-semiconductor field effect transistors Appl. Phys. Lett. 101, 133505 (2012) Top-gate staggered poly(3,3″′-dialkyl-quarterthiophene) organic thin-film transistors with reverse-offset-printed silver source/drain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…We can also infer that the minimum annealing temperature is approximately 500 °C. This is consistent with studies on low temperature annealed ohmic contact on GaN, in which the optimal temperature is often 500 °C or more, except for non‐alloy techniques such as the ones that use heavily doped GaN . The data on Ti/Al‐based scheme with recessed contacts do not necessarily follow the linear relationship as shown in Figure , meaning that the current flows by another conduction mechanism, such as direct contact with 2DEG.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We can also infer that the minimum annealing temperature is approximately 500 °C. This is consistent with studies on low temperature annealed ohmic contact on GaN, in which the optimal temperature is often 500 °C or more, except for non‐alloy techniques such as the ones that use heavily doped GaN . The data on Ti/Al‐based scheme with recessed contacts do not necessarily follow the linear relationship as shown in Figure , meaning that the current flows by another conduction mechanism, such as direct contact with 2DEG.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, lowering the annealing temperature is another challenge in ohmic contacts. One of the ways to realize low‐temperature‐annealed Au‐free ohmic contacts is using pre‐metal‐deposition treatments, such as recess etching under ohmic contact and regrown n + ‐GaN . However, these techniques increase the number of steps in the fabrication process of HEMTs, thus increasing the costs and causing a high level of defectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we were able to realize SAG with PAMBE, achieving a record low contact resistivity of 1.8 9 10 À8 X cm 2 for Ohmic contacts to an n-type GaN channel of a metalÀsemiconductor field-effect transistor (MESFET) 9 and an extremely low nonalloyed contact resistance of 0.6 X mm for contacts to a two-dimensional electron gas (2DEG) channel in an AlGaN/GaN high-electron-mobility transistor (HEMT). 10 These results not only demonstrate the advantage of SAG over the conventional contact scheme, but also indicate that SAG may be a better choice than ion implantation for fabricating Ohmic contacts. Furthermore, due to the damage-free nature of the SAG technique, we infer that it would provide higher breakdown voltage than ion implantation, which is crucial for high-power GaN devices.…”
Section: Introductionmentioning
confidence: 86%
“…In our previous studies, we were able to realize SAG by PAMBE, achieving a record low contact resistivity of 1.8 × 10 −8 Ω cm 2 and much enhanced peak drain currents for both GaN MESFET and HEMT . We also demonstrated that unlike ion implantation, the damage‐free PAMBE‐SAG technique is able to suppress the buffer leakage current and improve the breakdown characteristics .…”
Section: Introductionmentioning
confidence: 93%